Diagnosis and management of idiopathic pulmonary fibrosis: Thoracic Society of Australia and New Zealand and Lung Foundation Australia position statements summary. Issue 2 (20th November 2017) - Jo*, Helen E; Prasad*, Jyotika D; Troy, Lauren K; Mahar, Annabelle; Bleasel, Jane; Ellis, Samantha J; Chambers, Daniel C; Holland, Anne E; Lake, Fiona R; Keir, Gregory; Goh, Nicole S; Wilsher, Margaret; et al.
Abstract: Introduction: Idiopathic pulmonary fibrosis (IPF) is a fibrosing interstitial lung disease associated with debilitating symptoms of dyspnoea and cough, resulting in respiratory failure, impaired quality of life and ultimately death. Diagnosing IPF can be challenging, as it often shares many features with other interstitial lung diseases. In this article, we summarise recent joint position statements on the diagnosis and management of IPF from the Thoracic Society of Australia and New Zealand and Lung Foundation Australia, specifically tailored for physicians across Australia and New Zealand. Main suggestions: A comprehensive multidisciplinary team meeting is suggested to establish a prompt and precise IPF diagnosis. Antifibrotic therapies should be considered to slow disease progression. However, enthusiasm should be tempered by the lack of evidence in many IPF subgroups, particularly the broader disease severity spectrum. Non‐pharmacological interventions including pulmonary rehabilitation, supplemental oxygen, appropriate treatment of comorbidities and disease‐related symptoms remain crucial to optimal management. Despite recent advances, IPF remains a fatal disease and suitable patients should be referred for lung transplantation assessment.